2019
DOI: 10.1080/16138171.2019.1693143
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and gender in organized youth sports

Abstract: Sports are social, and the sociability of sports (e.g. individual experiences, group cohesion or generalised social trust) and its consequences (e.g. enjoyment, inclusion, or social capital) depends on the social networks in sports teams. In this study we investigate various types of social networks in sports-strong and weak-for boys and girls. We look at the number of social relations in each team (average degree), how centralised and hierarchical teams are, and how each team clusters and consists of subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Our study is among the first to explore how social relations in sports develop, and there are many crucial and interesting questions that need future research. Previous research has shown gender differences when it comes to social networks in general [32] and in sports [66]. A first challenge then is to adopt a gender perspective and go deeper into the question of how social relations develop within the context of sports for boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is among the first to explore how social relations in sports develop, and there are many crucial and interesting questions that need future research. Previous research has shown gender differences when it comes to social networks in general [32] and in sports [66]. A first challenge then is to adopt a gender perspective and go deeper into the question of how social relations develop within the context of sports for boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…Graph-level measures are based on the sociocentric approach, which conceptualizes social capital as a collective asset. Most studies within the category used graph-level measures to examine social capital in sports teams (Bergesen Dalen and Seippel 2019), regional innovation networks (Eklinder-Frick, Eriksson, and Hallén 2014; Muscio, Lopolito, and Nardone 2019), resource management (A. P. Fischer et al 2014; Rova and Sandström 2010), tourism (Birendra et al 2018), biodiversity conservation (Tuda and Machumu 2019), and agri-food (Ramirez et al 2018).…”
Section: Network Measures Of Social Capitalmentioning
confidence: 99%
“…The second step is to show the roster to respondents and ask them to check the listed names to see if they have specified relations. For instance, Bergesen Dalen and Seippel (2019) created a roster for thirty teams of athletes through a snowball sampling technique, in which the data collection started with the main author’s network of coaches and then expanded to other coaches who provided lists of their team members.…”
Section: Network Measures Of Social Capitalmentioning
confidence: 99%
“…It will be further discussed if the sport is also a medium for interaction between one human and another. Dalen and Seippel (2019) Good communication within an athlete's family will affect the athlete's performance in the field, besides this also affects how athletes communicate to other people such as coaches, sports friends, and even the community when the athlete is outside the training environment (Erdner & Wright, 2018). Li et al, (2017) revealed that a child who has a good relationship in the family can communicate well at school, and can interact well with other environments besides school.…”
Section: Graph 3 Bar Chart Of Family and Social Media Categories Of Social Interactionmentioning
confidence: 99%